Pentingnya Penaanaman Sikap Disiplin Pada Anak Usia 5-6 Tahun di Sekolah RAT Al Ishlah Gorontalo - Wiwid Asianti Mooduto; Rini Yanti Uaneto; Pupung Puspa Ardini; Sri Rawanti (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
Education of children's discipline is very important as a basis and preparation for the future. This is because each child has different characteristics and developments. In addition, attention to children is very necessary in the process of their education. One technique in the importance of discipline is the provision of reinforcement. This study aims to instill children's discipline through reinforcement techniques both verbally and nonverbally by giving praise or rewards to children. The method used is qualitative descriptive. The subjects of the study were 19 children aged 5-6 years at Rat Al Ishlah school, namely 10 boys and 9 girls. The results of the study showed that there was a problem with children's discipline with many factors that influence the level of success in the process of forming this discipline. Among them are factors of children's habits, both at home and in the surrounding environment.